Zuordnungsverfahren für Tauschbörsen - N., N.

Weitsichtigkeit zur Bildung stabiler Koalitionen - eine spieltheoretische Analyse - N., N.

Verhandeltes strategisches Verhalten - N., N.

Kronzeugenprogramme zur Aufdeckung von Kartellen - Eine spieltheoretische Analyse - N., N.

Eine ökonomische Analyse der Piraterie in zweiseitigen Softwaremärkten - N., N.

Kulturelle Unterschiede beim Lösen von Verhandlungsproblemen - N., N.

Productivity optimization through project matching - N., N.

Matching Mechanisms and Organ Exchange - N., N.

Cartel Fines in the European Union - N., N.

Anspruchsregeln in Verhandlungen - N., N.

Die Zusammenstellung eines Sortiments als Beispiel interdependenter Verhandlungen - N., N.

Matching in Netzwerken - N., N.

A Framework for Measurable Value Propositions of Mobile Applications - N., N.

Model-Based Product Configuration in Augmented Reality Applications - N., N.

Design and Implementation of a Crowd-based Prototype Validation Platform - N., N.

Design and Implementation of a ReconOS-based TensorFlow Lite Delegate Architecture - Jentzsch, Felix P.
Modern machine learning (ML) techniques continue to move into the embedded system space because traditional centralized compute resources do not suit certain application domains, for example in mobile or real-time environments. Google’s TensorFlow Lite (TFLite) framework supports this shift from cloud to edge computing and makes ML inference accessible on resource-constrained devices. While it offers the possibility to partially delegate computation to hardware accelerators, there is no such “delegate” available to utilize the promising characteristics of reconfigurable hardware. This thesis incorporates modern platform FPGAs into TFLite by implementing a modular delegate framework, which allows accelerators within the programmable logic to take over the execution of neural network layers. To facilitate the necessary hardware/software codesign, the FPGA delegate is based on the operating system for reconfigurable computing (ReconOS), whose partial reconfiguration support enables the instantiation of model-tailored accelerator architectures. In the hardware back-end, a streaming-based prototype accelerator for the MobileNet model family showcases the working order of the platform, but falls short of the desired performance. Thus, it indicates the need for further exploration of alternative accelerator designs, which the delegate could automatically synthesize to meet a model’s demands.

Approximate Pure Nash Equilibria in Congestion, Opinion Formation and Facility Location Games - Feldotto, Matthias
This thesis investigates approximate pure Nash equilibria in different game-theoretic models. In such an outcome, no player can improve her objective by more than a given factor through a deviation to another strategy. In the first part, we investigate two variants of Congestion Games in which the existence of pure Nash equilibria is guaranteed through a potential function argument. However, the computation of such equilibria might be hard. We construct and analyze approximation algorithms that enable the computation of states with low approximation factors in polynomial time. To show their guarantees we use sub games among players, bound the potential function values of arbitrary states and exploit a connection between Shapley and proportional cost shares. Furthermore, we apply and analyze sampling techniques for the computation of approximate Shapley values in different settings. In the second part, we concentrate on the existence of approximate pure Nash equilibria in games in which no pure Nash equilibria exist in general. In the model of Coevolving Opinion Formation Games, we bound the approximation guarantees for natural states nearly independent of the specific definition of the players' neighborhoods by applying a concept of virtual costs. For the special case of only one influential neighbor, we even show lower approximation factors for a natural strategy. Then, we investigate a two-sided Facility Location Game among facilities and clients on a line with an objective function consisting of distance and load. We show tight bounds on the approximation factor for settings with three facilities and infinitely many clients. For the general scenario with an arbitrary number of facilities, we bound the approximation factor for two promising candidates, namely facilities that are uniformly distributed and which are paired.

Combining Android Apps for Analysis Purposes - Zhang, Shikun

Modeling Crypto API usages in OpenSSL's EVP library - Selbach, Nils

Vertrauensbildung und Reputationssysteme auf digitalen B2B-Märkten - Ein klassifizierender Überblick - Nutt, Florian

There's an App for that - Ein Literaturüberblick über Erfolgsfaktoren für App-Downloads - Beckhoff, Yvonne Maria

Ideenbewertung durch die Crowd - Ein klassifizierender Literaturüberblick - Groh, Andreas

# Fail - Ein Literaturüberblick über Online-Bewertungen zu Produkt- und Dienstleistungsfehlern - Fath, Jerome Louis

Bewertung von Maschinen-generierten Geschäftsmodell-Ideen: Eine experimentelle Untersuchung - Seutter, Janina

Vandalism Detection in Crowdsourced Knowledge Bases - Heindorf, Stefan

A Bitstream-Level Proof-Carrying Hardware Technique for Information Flow Tracking - Keerthipati, Monica
Secure hardware design is the most important aspect to be considered in addition to functional correctness. Achieving hardware security in today’s globalized Integrated Cir- cuit(IC) supply chain is a challenging task. One solution that is widely considered to help achieve secure hardware designs is Information Flow Tracking(IFT). It provides an ap- proach to verify that the systems adhere to security properties either by static verification during design phase or dynamic checking during runtime. Proof-Carrying Hardware(PCH) is an approach to verify a functional design prior to using it in hardware. It is a two-party verification approach, where the target party, the consumer requests new functionalities with pre-defined properties to the producer. In response, the producer designs the IP (Intellectual Property) cores with the requested functionalities that adhere to the consumer-defined properties. The producer provides the IP cores and a proof certificate combined into a proof-carrying bitstream to the consumer to verify it. If the verification is successful, the consumer can use the IP cores in his hardware. In essence, the consumer can only run verified IP cores. Correctly applied, PCH techniques can help consumers to defend against many unintentional modifications and malicious alterations of the modules they receive. There are numerous published examples of how to use PCH to detect any change in the functionality of a circuit, i.e., pairing a PCH approach with functional equivalence checking for combinational or sequential circuits. For non-functional properties, since opening new covert channels to leak secret information from secure circuits is a viable attack vector for hardware trojans, i.e., intentionally added malicious circuitry, IFT technique is employed to make sure that secret/untrusted information never reaches any unclassified/trusted outputs. This master thesis aims to explore the possibility of adapting Information Flow Tracking into a Proof-Carrying Hardware scenario. It aims to create a method that combines Infor- mation Flow Tracking(IFT) with a PCH approach at bitstream level enabling consumers to validate the trustworthiness of a module’s information flow without the computational costs of a complete flow analysis.

Using Just-in-Time Code Generation to Transparently Accelerate Applications in Heterogeneous Systems - Vaz, Gavin Francis

On Scheduling with Setup Times - Mäcker, Alexander

Autonomous Operation of High-Performance Compute Nodes through Self-Awareness and Learning Classifiers - Hansmeier, Tim

Scaling, placement, and routing for pliable virtualized composed services - Dräxler, Sevil

Essays on Crowd Based Idea Evaluation - Empirical Evidence from an Anonymous Online Crowd - Görzen, Thomas

Organic Programming of Dynamic Real-Time Applications - Khaluf, Lial

Rational Secure Multiparty Computation - Bröcher, Henrik

Requirements Engineering im OTF-Computing: Informationsextraktion und Unvollständigkeitskompensation mittels domänenspezifischer Wissensbasis - Friesen, Edwin

Analyzing Data Usage in Array Programs - Haltermann, Jan

Implementation and Evaluation of Authenticated Data Structures Using Intel SGX Enclaves - N., N.

Optimizing Sales Channel Performance with Digital Experiments in the Crafting Industry - Althaus, Steffen

Essays on Drivers and Economic Outcomes of Online-Reviews - Gutt, Dominik

Scheduling Algorithms for Multi-Operation Jobs with Setups on a Single Machine - Pukrop, Simon

Efficient Finite-Field Arithmetic for Elliptic Curve Cryptography in Java - Pilot, Matthias

Implementation and Comparison of Elliptic Curve Algorithms in Java - Scholz, Swante

Vertrauensbildung und Reputationssysteme auf digitalen B2B-Märkten - Ein klassifizierender Überblick - Kilic, Mehmet

Gib anderen dein Zuhause - Eine deskriptive Analyse der Ausbuchungsrate von Inseraten auf Airbnb - Yilmaz, Melih

Conception of a digital Sales Bonus System based on Blockchain Technology - Rodehutskors, Luca Maurizio

Entwicklung eines Frameworks für Geschäftsmodelle im On-The-Fly Computing - Dirksen, Daniel

Worüber sprechen Ihre Kunden? Anwendung und Evaluation von Text Mining auf Online-Kundenbewertungen am Beispiel von Google Maps Reviews - Lo Tauro, Santo Stefan

Haben B2B-Kunden auch Gefühle? Eine semantische Analyse von Online-Kundenbewertungen auf digitalen B2B-Märkten - Post, Hannes

Kreativität in der Wirtschaftsinformatik: Ein systematischer Literaturüberblick von Experiment-Designs - Henke, Lena

Kreativitäts-Experimente in der Wirtschaftsinformatik - Ein systematischer Literaturüberblick - Recker, Davide Pietro

The Digital CV - Ein Literaturüberblick über Onlien-Bewertungen in Online Labor Markets - Meier zu Wickern, Joelle

Eine deskriptive Analyse der Verteilung von Online-Bewertungen auf digitalen B2B-Märkten - Petrovic, Bogoljub

Eine semantische Analyse von Online-Bewertungen auf digitalen B2B-Märkten - Schulte, Tristan Aaron

Entwicklung eines Rahmenwerks zur Evaluation von Geschäftsmodellen zur Entscheidungsunterstützung für Kooperationen mit Startups am Beispiel der Schüco International KG - Golis, Miriam

Feasibility study on the use of Hypermedia/HATEOAS using an example of a RESTful API from the financial services environment based on OpenAPI/Swagger - Brockmeier, Felix Karl

Mechanismen zur Aggregation der Meinungen einer Crowd - Ein klassifizierender Literaturüberblick - Schiller, Leo

The effects of driver variables on online review metrics: A meta-analysis - Selig, Maximilian Julius

Share at all Costs? Ein Literaturüberblick zur Privacy Risk Calculus Theory - Althaus, Maike

Sozioökonomische Implikationen des Sharing Economy Trends - Rohde, Lukas

Reputation in der Sharing Economy - Eine ökonometrische Analyse des Zusammenhangs zwischen Online-Bewertungen und Nachfrage am Beispiel von Airbnb - Bentfeld, Bastian

Stoppt das Sharing? Ökonometrische Untersuchungen zur gesetzlichen Einschränkung von Airbnb - Agethen, Christopher Heinrich

It's a match! - Entwicklung eines Ansatzes zur Identifikation von Cross-Listings auf Airbnb und TripAdvisor - Wegener, Moritz

Do Online Ratings Matter in the Sharing Economy? Analyzing the Impact of Online Ratings on Demand on Airbnb - Gerzen, Gabriele

Möglichkeiten und Grenzen crowdbasierter Ideenbewertung - Ein systematischer Literaturüberblick - Resch, Tim

Externe Stimuli zur Geschäftsmodell-Ideengenerierung: Ein Experimenteller Ansatz - Milder, Christoph

Efficient parallel branch-and-bound search on FPGAs using work stealing and instance-specific designs - Riebler, Heinrich

"Data-Driven Mergers" in digitalen Märkten - eine wettbewerbspolitische Analyse - Lütkevedder, Dennis

On the Implications of Big Data for Competition Policy - Big data, Market power, Competition law - Memon, Uzair Ahmed

Risiken und Gefahren von Marktmacht in digitalen Märkten - eine wettbewerbspolitische Analyse - Milczarek, André

Digitale Märkte - Zu den Auswirkungen von Big Data auf Marktmacht und die Bildung von Kartellen - Heinrichs, Fabian

Anreizwirkungen der Bonusregelung - Eine wettbewerbspolitische Analyse - Fortmeier, Julia

The intersection of privacy and competition law - Lessons from data-driven mergers - Hagedorn, Carolin

Die Akquisition von Double Click durch Google - eine wettbewerbspolitische Analyse - Ayyildiz, Berfin

Merger Analysis in Data-Driven Markets - An Economic Policy Perspective - Shelepova, Ekaterina

Marktmacht in digitalen Märkten - Shanmugaratnam, Suganya

The Effectiveness of Leniency Programs and Whistleblowing in Discouraging Cartel Activities - Faizan, Ahmed

Intermediaries in Networks - N., N.

Logrolling-Prozess: Theorie und formale Darstellung einer verhandlungsunterstützenden Methode - N., N.

Stability in two-sided matchings with asymmetric information - N., N.

Sincere and Sophisticated Players in Matching Markets - N., N.

Mechanismen zur Informationsgewinnung in Verhandlungen - N., N.

Die faire Verteilung unteilbarer Güter - N., N.

Axiomatisierungen des Banzhaf-Wertes - N., N.

Compatibilities in Matching Mechanisms - N., N.

Faire Aufteilung von unteilbaren Gütern: Untersuchung von Algorithmen auf Effizienz und Neidfreiheit - N., N.

Anwendung und Vergleich von Verhandlungslösungen auf das Netzwerk-Design-Problem - N., N.

Verhandlungen mit Intermediären in IT-Märkten: eine spieltheoretische Analyse - N., N.

A bargaining model for relative profit and market share delegation contracts - N., N.

Wettbewerb in Märkten für Dienstleitungen mit uninformierten Kunden - N., N.

Der Shapley-Wert als Index für phylogenetische Diversität - N., N.

Student's school matching mechanisms in the US - N., N.

Conception of a digital Sales Bonus System based on Blockchain Technology - N., N.

Implementing a Real-time System on a Platform FPGA operated with ReconOS - Lienen, Christian

Datengetriebene Geschäftsmodelle: Ein Literaturüberblick - Arendt, Lukas Sebastian

Kundenbewertungen und Produktnachfrage: Eine ökonomische Analyse - Maurer, Alexandra

The Segmentation of Video-On-Demand Consumers - Michels, Luisa Juliane

Sentiment Analysis of User-generated Ratings in the Sharing Economy - Walter, Miriam

Restaurant reputation and meal prices: empricial evidence from the German restaurant industry - Korn, Hanna

Korrektheitsbeweise für Muster von Servicekompositionen - Rautenberg, Kai

Static Scheduling Algorithms for Heterogeneous Compute Nodes - Schnuer, Jan-Philip

Evaluation of OpenCL-based Compilation for FPGAs - Croce, Marcel